Effects of resveratrol on drug‐ and carcinogen‐metabolizing enzymes, implications for cancer prevention. Issue 1 (31st January 2017) - Guthrie, Ariane R.; Chow, H‐H. Sherry; Martinez, Jessica A.
Abstract: Resveratrol is a polyphenol found in grape skins and peanuts that has demonstrated many health benefits including protection against aging, cardiovascular and metabolic disease, neurological decline, and cancer. The anticancer properties of resveratrol have been attributed to a variety of mechanisms, including its general inhibition of phase I metabolism and induction of phase II metabolism. The effects of resveratrol on these enzymes, however, are still unclear, as in vitro evidence often contrasts with animal studies and clinical trials. Reasons for these variances could include the low bioavailability of resveratrol and the effects of resveratrol metabolites. Due to resveratrol's interactions with drug‐metabolizing enzymes and drug transporters, individuals concurrently taking pharmacological doses of resveratrol with other supplements or medications could potentially experience nutrient‐drug interactions. This review summarizes the known effects of resveratrol and its main metabolites on drug metabolism in order to help characterize which populations might benefit from resveratrol for the prevention of cancer, as well as those that may need to avoid supplementation due to potential drug interactions.